A New Preclearance Coverage Formula: Renewing the Promise of the Voting Rights Act - Oluoma Kas-Osoka (Washington University Journal of Law & Policy, 2015)
The Voting Rights Act of 1965 (VRA) sought to mitigate the disenfranchisement experienced by African American voters by providing targeted reforms to electoral processes at the state level. This Note examines many of the legal challenges to the VRA subsequent to its enactment that have effectively disassembled its intended protections. This Note also examines the impact of barriers to voting and Congressional attempt to secure the right to vote for minority citizens. This Note argues that the proposed 2014 amendment to the VRA is not effective with regards to protecting the interests of minority voters and proposes a new coverage formula to effectuate the overall purpose of the statute.
Keywords: Voting; Voting Rights Act; VRA; Minority Voters; 2014 Amendment; Amendment; Civil Rights